Evaluasi Fisik Dan Uji Aktivitas Sediaan Hair Tonic Ekstrak Bunga Telang (Clitoria ternatea L.) Terhadap Pertumbuhan Rambut Kelinci Jantan (Oryctolagus cuniculus) - Lestari, Alfi; Ulfa, Ade Maria; Saputri, Gusti Ayu Rai (Peneliti.net, 2024)
Hair tonic is one of the cosmetic products that can prevent hair loss. Striped flowers (Clitoria ternatea L) have the potential to overcome hair loss because they contain antioxidant and anti-inflammatory compounds, namely flavonoids, alkaloids, tannins, saponins, and others. The purpose of this study was to make a hair tonic preparation containing telang flower extract and test its activity on hair growth, physical evaluation of hair tonic preparations and determine the best hair growth activity. This research uses ultrasonic method with solvent aquadest. Hair tonic is made with concentrations of 2.5%, 5%, and 10%. The preparation is applied to the skin of rabbits daily for 28 days and the length of hair is measured on days 7, 14, 21 and 28 using calipers. Minoxidil is used as a positive control. The test results showed that F1(2.5%) and F2(5%) had hair growth activity seen from the sig value of <0.05 which was significantly different from F3(10%) and K(+). F3(10%) has the best hair growth activity which is not significantly different from K(+) with an average hair length of 7.56 1.91 and a sig value of >0.05. Hair tonic preparations of telang flower extract (Clitoria ternate L) F1, F2 and F3 meet the evaluation of physical preparations in accordance with SNI 19-4955-1998.